Innovative building materials and sick building syndrome: Liabilities of manufacturers and importers of defective materials - Evans, Philip (School of Business Law, Curtin Business School, Curtin University of Technology, 2008)
The influence on indoor air quality of volatile organic compounds contained in a wide range of building materials has been known for some time. However in order to reduce materials costs and construction times, builders are increasingly using alternative innovative construction materials which may contain hazardous compounds. This paper firstly considers the use and composition of innovative materials and discusses the legal issues arising from Sick Building Syndrome with particular emphasis on Part VA of the Trade Practices Act 1974 (Cth) which creates a statutory right to damages in the event that goods are defective and injury or damage is suffered as a result, by imposing a strict liability for manufacturers and importers of defective goods without being constrained by the limitations at common law.